Controlled self-assembly of quantum dot-block copolymer colloids in multiphase microfluidic reactors - Wang, Chih-Wei (Langmuir : the ACS journal of surfaces and colloids, 2010)
The controlled self-assembly of large compound quantum dot micelles (QDCMs), consisting of constituents of polymer-stabilized quantum dots (QDs) and amphiphilic polystyrene-b-poly(acrylic acid) stabilizing chains, in gas-liquid segmented microfluidic reactors is demonstrated. Self-assembly is initiated by fast mixing of water with the polymer constituents via chaotic advection, as liquid plugs containing reactants move through a sinusoidal mixing channel. The resulting QDCMs are then processed within a postformation channel, where circulating flow patterns develop within the liquid plugs, followed by off-chip quenching and analysis by transmission electron microscopy (TEM). Particle processing via circulating flow is found to involve a combination of particle growth via collision-induced coalescence and shear-induced particle breakup. The final mean QDCM sizes represent kinetic states arising from the competition between these two mechanisms, depending on tunable chemical and flow parameters. A systematic investigation of the experimental variables that influence particle size and polydispersity, including water concentration, flow rate, and the gas-to-liquid flow ratio, is conducted, demonstrating tunability of QDCM sizes in the range of approximately 40-140 nm. The importance of shear-induced particle breakup in the limit of high shear is illustrated by a common minimum particle size, 41 +/- 1 nm, which is achieved for all water contents by increasing the total flow rate to sufficiently high values